2021
DOI: 10.1155/2021/5594305
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Working Memory and Resting-State fMRI by tDCS of the Right Frontoparietal Network

Abstract: Many cognitive functions, including working memory, are processed within large-scale brain networks. We targeted the right frontoparietal network (FPN) with one session of transcranial direct current stimulation (tDCS) in an attempt to modulate the cognitive speed of a visual working memory task (WMT) in 27 young healthy subjects using a double-blind crossover design. We further explored the neural underpinnings of induced changes by performing resting-state fMRI prior to and immediately after each stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Ishibashi et al reported that the brain processing areas that recognize and use tools are the IPL and ventral premotor cortex [ 23 ]. Pupíková et al reported on action reappraisal mechanisms during object and tool recognition by measuring resting-state fMRI before and after transcranial direct current stimulation targeting the right frontoparietal network (FPN) [ 24 ]. Federico et al also reported on how various sources of information are used for the motor behaviors performed by humans [ 16 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ishibashi et al reported that the brain processing areas that recognize and use tools are the IPL and ventral premotor cortex [ 23 ]. Pupíková et al reported on action reappraisal mechanisms during object and tool recognition by measuring resting-state fMRI before and after transcranial direct current stimulation targeting the right frontoparietal network (FPN) [ 24 ]. Federico et al also reported on how various sources of information are used for the motor behaviors performed by humans [ 16 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Federico et al also reported on how various sources of information are used for the motor behaviors performed by humans [ 16 , 25 ]. This action reappraisal is considered to be the act of integrating multiple different sensory information and connecting it to actual action [ 24 ]. In this research, various pieces of information for the four objects, the motion of moving the hand, the sensation of touching the object, and the emotion produced by gripping the object, are considered to be integrated to recognize the objects.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it has been also demonstrated that persistent and CP is associated with alteration in the activity of the Default Mode Network (DMN) and the connectivity between its nodes (medial prefrontal cortex, lateral parietal cortex/angular gyrus, and posterior cingulate cortex/precuneus) (Baliki et al, 2008 ; Tessitore et al, 2013 ), consistently related with WM dysfunctions (Mazoyer et al, 2001 ; Sambataro et al, 2010 ), coping strategies (Santarnecchi et al, 2018 ) and several MH pathological conditions (refer to Broyd et al, 2009 for a review) (Broyd et al, 2009 ). Recent evidence from non-invasive brain stimulation (NIBS) indicates that stimulation of nodes of the DMN is associated with WM performance in healthy adults (Pupíková et al, 2021 ) or could be a promising therapeutic approach to reduce cognitive and mood disorders in different pathologies (Alexoudi et al, 2019 , 2020 ; Chou et al, 2020 ). Finally, it has been recently shown that transcranial direct current stimulation (tDCS) modulates pain perception, but depending on the age, the brain target should be M1 (for older adults) or DLPFC (for younger adults), although both sides increased WM ability (Saldanha et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, speci c hypotheses have been generated about the involvement of such fronto-temporo-parietal areas in the context of the actionreappraisal approach (e.g., . Although the scienti c debate about the neural correlates of the action reappraisal mechanism is very far from being concluded, increasing and converging support to the action reappraisal idea comes from studies that highlighted the involvement of speci c brain networks involved in integrating information about action and objects across different modalities (e.g., Chen, Garcea, Jacobs & Mahon, 2018;De Bellis et al 2020;Lambon Ralph, Jefferies, Patterson & Rogers, 2017;Wurm & Caramazza 2019;Lesourd et al, 2021;Pupíková, Šimko, Gajdoš, Rektorová, 2021). Signi cantly, a most recent fMRI/tDCS study (Pupíková et al, 2021) demonstrated how stimulating the fronto-parietal network with twenty minutes of 2mA anodal tDCS increased the recognition performance of participants involved in a yes-no object recognition task which was similar to the one developed by Federico and Brandimonte (2020), hence providing the rst solid causal evidence for the action reappraisal mechanism.…”
Section: Discussionmentioning
confidence: 99%